Management of the red deer (Cervus elaphus Linnaeus, 1758) population in the Azov-Syvash National Park, Ukraine - Volokh, Anatolii; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович (My University, 2018)
The red deer (Cervus elaphus Linnaeus, 1758), an object of our research, is a complex hydrid raised in Askania Nova Reserve. There, in 1902–1950, were at first crossed the Central European deer (C. elaphus hippelaphus Erxleben, 1777) and Siberian red deer (C. elaphus sibiricus Severtzov, 1873), then their hybrids were crossed with the Siberian red deer, Caspian red deer (C. maral Ogilby, 1840), Crimean deer (C. elaphus brauneri Charlemagne, 1920), Manchurian deer (C. elaphus xanthophygus Milne-Edwards, 1867) and the wapiti (C. elaphus canadensis Erxleben, 1777). Since 1961, the Bactrian deer (C. elaphus bactrianus Lydekker, 1902) (Тreus 1968) was added to the reproduction. The breed received as a result of this cross-breeding was called the Askanian steppe maral. Artificial relocation has formed a several groups of this animal in Ukraine isolated from each other and being independent populations. The largest one is located in the steppe zone in the Azov-Syvash National Nature Park (NNP) on Biriuchyi Peninsula (the Sea of Azov). The open landscape of the island, covering an area of 6400 ha, in 2018 has supported more than 1000 deer (Fig. 1), more than 1600 fallow deer and over 100 onagers.
Keywords: area; hybridation; hunting; mammals; management; population; red deer; Cervus elaphus; steppe zone; trophy; Ukraine